2018
DOI: 10.1111/1750-3841.14100
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Saccharomyces cerevisiae on Perlite Beads for the Decontamination of Aflatoxin M1 in Milk

Abstract: The immobilization of Saccharomyces cerevisiae cells on perlite beads can be used to detoxify AFM1-contaminated milk. The perlite can provide a perfect support for immobilization. With respect to qualitative properties, 20 min, was suggested as the optimum time for milk decontamination. This study indicated that the detoxification of contaminated milk using immobilized S. cerevisiae cells on the perlite support did not affect the different properties of detoxified milk. This method can lead to a practical solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The proposed method reported by Foroughi et al in 2018 consists of immobilizing yeast such as Saccharomyces cerevisiae on perlite support to detoxify AFM1-contaminated milk [146]. The results showed a significant reduction in AFM1 concentration for all tested milk samples with various initial AFM1 contents.…”
Section: Prospective Industrial Applicationsmentioning
confidence: 99%
“…The proposed method reported by Foroughi et al in 2018 consists of immobilizing yeast such as Saccharomyces cerevisiae on perlite support to detoxify AFM1-contaminated milk [146]. The results showed a significant reduction in AFM1 concentration for all tested milk samples with various initial AFM1 contents.…”
Section: Prospective Industrial Applicationsmentioning
confidence: 99%
“…Foroughi et al () reported a successful yeast immobilization on the perlite support for detoxification of AFM1 contaminated milk and confirmed the safety of ceramic beads by determination of remaining silicon and aluminum.…”
Section: Resultsmentioning
confidence: 91%
“…The immobilization of S . cerevisiae has provided a decontamination process with a higher performance because of its practical benefits compared with a traditional free cell system (Foroughi et al ; Rahaie et al ). The cell immobilization technique provides a continuous decontamination process as well as higher yeast cell densities and metabolic activity in the biofilter, which leads to a shorter AF decontamination time (Verbelen et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Lately, Foroughi et al (2018) have suggested a method to detoxify AFM 1 -contaminated milk by immobilizing yeast such as S. cerevisiae on perlite support. The results revealed a high significant removal of AFM 1 from milk samples where the highest detoxification percentage reached was 81.3% without altering the physicochemical properties of milk.…”
Section: Application Of Biological Detoxification Processes In the Fo...mentioning
confidence: 99%